Spacetimes with Pseudosymmetric Energy-momentum Tensor - Mallick, Sahanous; De, Uday Chand (Communications in Physics, 2016)
The object of the present paper is to introduce spacetimes with pseudosymmetricenergy-momentum tensor. In this paper at first we consider the relation \(R(X,Y)· T=fQ(g,T)\), that is, the energy-momentumtensor \(T\) of type (0,2) is pseudosymmetric. It is shown that in a general relativistic spacetimeif the energy-momentum tensor is pseudosymmetric, then the spacetime is also Ricci pseudosymmetricand the converse is also true. Next we characterize the perfect fluid spacetimewith pseudosymmetric energy-momentum tensor. Finally, we consider conformally flat spacetime withpseudosymmetric energy-momentum tensor.